Rasisme dan Penerapan Pasal Makar terhadap Kebebasan Ekspresi Politik Papua - Herlambang P. Wiratraman (Undang: Jurnal Hukum, 2021)
Freedom of political expression has not been fully guaranteed in the Indonesian legal system. One of the most prominent in the legal debate is the matter of treason (makar) charges against political expressions of self-determination. In the case of Papua, many Papuans have been detained, criminalised, and even killed because of their political expression. Interestingly, the Constitutional Court, through its decision Number 7/PUU-XV/2017, provided guidance in its ‘ratio decidendi’ argument, specifically the interpretation of treason phrases in the Criminal Code. Interpretation is given by the Constitutional Court after seeing the reality that law enforcement has been arbitrarily abused by the application of the treason article. This is contrary to the freedom of association, opinion and expression, as guaranteed in the 1945 Constitution of the Republic of Indonesia. This article discusses how the application of the phrase treason in law enforcement, especially in connection with the conviction of many Papuans after the Surabaya anti-racism rallies in September 2019. A number of district court decisions on dozens of convicted Papuans show that the legal system that guarantees freedom of political expression has not changed much and law enforcement in fact emphasises the position of racial discrimination and is far below the standard of human rights law. Abstrak Kebebasan ekspresi politik belum sepenuhnya dijamin dalam sistem hukum Indonesia. Salah satu yang paling mengemuka dalam perdebatan hukum adalah soal tuduhan makar terhadap ekspresi politik menentukan nasib sendiri. Dalam kasus Papua, tidak sedikit jumlah warga Papua yang ditahan, dikriminalkan, hingga tewas terbunuh karena soal ekspresi politiknya. Menariknya, Mahkamah Konstitusi melalui putusannya Nomor 7/PUU-XV/2017 memberikan panduan dalam argumen ratio decidendinya, khusus interpretasi frasa makar dalam Kitab-Undang-Undang Hukum Pidana. Penafsiran diberikan oleh Mahkamah Konstitusi setelah melihat realitas penegakan hukum telah banyak disalahgunakan penerapan pasal makar. Hal demikian bertentangan dengan kebebasan berkumpul, berpendapat dan berekspresi, sebagaimana dijamin dalam Undang-Undang Dasar Negara Republik Indonesia Tahun 1945. Artikel ini membahas bagaimana penerapan frasa makar dalam penegakan hukumnya, khususnya berkaitan dengan dipidananya banyak warga Papua setelah aksi anti rasisme Surabaya pada September 2019. Sejumlah putusan pengadilan negeri atas puluhan warga Papua yang dipidana tersebut memperlihatkan sistem hukum yang menjamin kebebasan ekspresi politik tidak banyak berubah dan penegakan hukum justru menegaskan posisi diskriminasi rasial serta jauh dari standar hukum hak asasi manusia.